Interventional Cardiovascular Magnetic Resonance Imaging: A New Opportunity for Image-Guided Interventions - Saikus, Christina E. (2009)
Cardiovascular magnetic resonance (CMR) combines excellent soft-tissue contrast, multiplanar views, and dynamic imaging of cardiac function without ionizing radiation exposure. Interventional cardiovascular magnetic resonance (iCMR) leverages these features to enhance conventional interventional procedures or to enable novel ones. Although still awaiting clinical deployment, this young field has tremendous potential. We survey promising clinical applications for iCMR. Next, we discuss the technologies that allow CMR-guided interventions and, finally, what still needs to be done to bring them to the clinic.